Makna Tari Jaranan sebagai Media Komunikasi: Studi Kasus Paguyuban Tri A Tunggal Kabupaten Tangerang - Dea Febrianti, Rias Mizar; Khairani, Aulian; Rahayu, Riza Gusti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Tri A Tunggal association serves as a platform to preserve and sustain traditional dance arts, a place to channel talents and act as a communication medium to convey cultural, moral, and identity messages of the Nusantara society, particularly Java. The theory used in this research is the symbolic interaction theory. The method used is a case study through interviews and field observations. The results of this research show that the association involves its members in the interpretation of symbols in the dance, which not only serves as entertainment but also strengthens the relationships among members and conveys traditional values to the community. This highlights the importance of preserving tradition and culture in every performance to spark public interest in sustaining traditional arts.